ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY IN THE STAY PERMIT SECTION ON THE SATISFACTION OF IMMIGRATION SERVICE USERS AT THE CLASS I IMMIGRATION OFFICE SPECIALLY TPI NGURAH RAI - Tengku Ezy Andika; Sugiharto; Meilita Tryana Sembiring (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to find out whether Physical Evidence, Reliability, Responsiveness, Guarantee and Empathy simultaneously and partially influence the satisfaction of Immigration service users at the TPI Ngurah Rai Special Class I Immigration Office. This research uses questionnaire data with a sample size of 100 people using the Slovin formula. Data processing uses SPSS software and this research uses Double Linear. The research results show that the variables physical evidence, reliability, responsiveness and guarantee do not have a significant influence on service user satisfaction at the TPI Ngurah Rai Special Class I Immigration Office. The empathy variable has a significant influence on service user satisfaction at the TPI Ngurah Rai Special Class I Immigration Office. Taken together, the variables physical evidence, reliability, responsiveness, assurance and empathy have a significant effect on service user satisfaction at the TPI Ngurah Rai Special Class I Immigration Office.